Assessing Coral Reef Health in Northern Waters of Penata Besar Island West Kalimantan - Bariah, Anisah; Safitri, Ikha; Nurrahman, Yusuf Arief; Sofiana, Mega Sari Juane; Helena, Shifa; Faizal, Ibnu (UIN Sunan Gunung Djati Bandung, 2024)
Penata Besar Island is designated as one of the Coastal and Small Island Conservation Areas (KKP3K) in West Kalimantan, is a critical site for conserving coral reefs and reef fish. Currently, global climate change and anthropogenic activities have exacerbated coral reef bleaching worldwide. In the context of escalating global climate change and human-induced threats, this study evaluates the health condition of coral reefs in the northern waters of Penata Besar Island, Bengkayang Regency. An exploratory approach was employed, utilizing the Line Intercept Transect (LIT) method across four stations at two distinct depths (2-3 m and 5-6 m). The results revealed that coral cover varied with depth. At a depth of 2-3 m, live coral coverage was between 51.2% and 62.4%, classified as good, while at 5-6 m, coverage ranged from 30.4% to 49.4%, categorized as fair. Coral Massive (CM) was the predominant growth form observed. The diversity index (H') ranged from low to medium, the Evennes index (E) from medium to high, and the dominance index (C) was categorized as low. These findings highlight the varying health of coral reefs in different depths and provide a basis and essential insights for targeted conservation efforts.